Studi Tingkat Pengetahuan Mengenai Vitamin D pada Pengemudi Becak di Surabaya - Rivan Virlando Suryadinata; Amelia Lorensia; Dwi Wahyuningtyas (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2020)
Introduction: Lack of vitamin D in the body is often associated with various diseases, especially against respiratorydiseases. This can be exacerbated by conditions of air pollution and smoking. In addition, the level of education andchanges in lifestyle patterns in the community such as food processing, consumption, lack of physical activity andsocial environment further aggravate the risk of vitamin D deficiency. One of the livelihoods at risk of experiencingvitamin D deficiency is a pedicab driver. Knowledge of the importance of the role of vitamin D in risk groups isneeded to increase awareness, provide prevention independently. Prevention can be carried out independently, ifthe community has the correct understanding and knowledge of vitamin D. Aim of the study: The purpose of thisstudy is to determine the level of knowledge of the importance of vitamin D in pedicap drivers in Surabaya. Method:This research is an observational study with cross sectional method through the filling of the vitamin D. knowledgequestionnaire. Results and Discussions: The results of the research that have been obtained will be describeddescriptively to see the description of the knowledge of pedicap drivers in Surabaya. The sampling technique in thisstudy used purposive sampling. The sample used was 150 pedicap drivers in Surabaya. The results showed thatpedicab drivers have a low level of knowledge about the importance of vitamin D to health. Conclusion:Conclusions of various factors can influence the level of vitamin D knowledge of pedicab drivers, so that the rightintervention is needed.